St. Augustine, his confessions, and his influence - Rorem, Paul (Mapping the tradition series, 2019)
"This book introduces Augustine of Hippo and his influence on Christian theology. Part one works through all thirteen books of the Confessions ... Part two sketches the medieval reception of the Augustinian theological legacy ..."--